Transitioned Media A Turning Point into the Digital Realm - Einav, Gali.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2010)
The media industry is in transition. While some changes are readily apparent, we have not even begun to understand the impact of others. The result is one of the most fascinating times in the history of media. As digital technologies accelerate the pace of change in all facets of our lives, researchers and practitioners are exploring its impact on traditional media and social interaction. Transitioned Media brings together leading academics and media industry executives to identify and analyze the most transformative trends and issues. Themes include the effect of digital technologies on consumer behavior, new approaches to advertising and branding, social networks, the blogosphere and impact of (3z(Bcitizen(3y (Bjournalism, music and intellectual property rights, digital cinema, and video games. Underlying the chapters is an economic perspective, with an emphasis on how new business models are being developed that take the social dimensions of digital technologies into account. The result is a unique perspective on the digital media landscape and the forces that will shape it in the future.s
Introduction: The End of Media As We Know It? -- Introduction: The End of Media As We Know It? -- The Changing World of Advertising and Consumer Behavior -- TV for the Twenty-First Century: The Video Ad Model in Transition -- Branded Entertainment: How Advertisers and Networks Are Working Together to Reach Consumers in the New Media Environment -- The Evolution of Cross-Platform Media Use in the United States: Insights from Consumer Research and NBC Universal$1 (Bs (3z(BOlympic Research Lab(3y (B-- The Changing Face of Traditional Media: The News Business Case Study -- We Interrupt this Program $1! = (BThe Cosmic Change in the (3z(BNews Business(3y (B-- Mobile Social Networking and the News -- Parsing the Online Ecosystem: Journalism, Media, and the Blogosphere -- Media Reinvented: Case Studies of Transitioning into a Digital Age -- The Transition to Digital TV: A Case Study of HDTV -- The Fat Lady Still Sings: Bringing Music into the Digital Age -- How Cinema Is Digital -- Thumb Wars: Body and Mind in Video Games.s
Keywords: Economics; Economic policy; Mass media; Economics/Management Science; Media Management; Economic Policy; Innovation/Technology Management